Environmental Geology of Halifax Harbour, Nova Scotia - Fader, Gordon; Buckley, Dale (Geoscience Canada, 1995)
Summary This paper demonstrates the importance of integrated studies of marine geology and geochemistry in the environmental management of an urbanized coastal inlet, using Halifax Harbour, Nova Scotia, as an example. The harbour receives 170 million litres of raw sewage per day; other sources of contamination include landfills, industrial activity, surface run off and dredging.The level of contamination by metals insurficial sediments in Halifax Harbour isamong the highest anywhere recorded in marine harbours, and is a result of sediment trapping and lack of flushing. Geological and océanographie conditions strongly influence the present environmental quality of the harbour; assessment of environmental quality, and the design of wastewater management systems in urban harbours, are fundamentally dependant on detailed knowledge of sediment transport, deposition and erosion.